The Impact of Renal Lower Pole Radiographic Anatomy on the clearance of Stone fragments after Extracorporeal Shock wave Lithotripsy (Medical Forum Monthly, 2024)
Objectives: 1. To determine the frequency of clearance of stone fragments after extracorporeal shock wave lithotripsy (ESWL) for isolated lower pole renal calculi. 2. To compare the average Lower Infundibular diameter and lower infundibulo-pelvic angle (L-IPA) between patients with residual stone fragments and those who become stone free after extracorporeal lithotripsy (ESWL) for isolated lower pole renal calculi. Study design: Descriptive Study. Place and Duration of Study: This study was conducted at Department of Urology, Liaquat National Postgraduate Medical Centre, Karachi from June 2006 to June 2010. Materials and Methods: One Hundred patients of either sex, aged > 14 years with isolated lower pole calculi (LPC) of <20mm undergoing ESWL were included in the study, while patients with lower pole calculi > 20mm, multiple renal calculi, congenitally distorted pelvi-calyceal anatomy, with concomitant Ureteric calculi, with decreased urine output due to renal insufficiency, with Hydronephrosis, with previous pyelo-uretral surgery, who required ancillary procedures e.g. Ureteroscopy, DJ Stent insertion were excluded from the study. The confirmation of stone in lower pole and LPC anatomy (width of the infundibulum and lower infundibulo-pelvic angle) were viewed on the IVU. The Infundibular width was measured as the narrowest point of the infundibulum. The L-IPA was determined in two axes, the ureteropelvic axis and the infundibulo-pelvic axis. Results: Frequency of clearance of stone fragments after ESWL for lower pole renal calculi was 82%. Average L IPA was significantly higher in those who become stone free after ESWL than patients with residual stone fragments (79.34 ± 8.33 vs. 64.56 ± 5.53, p<0.001). Average Lower Infundibular diameter was slightly higher in stone free patients after ESWL but not statistically significant (5.02 ± 0.76 vs. 4.89 ± 0.78, p=0.631). Conclusion: Successful ESWL is sensitive to lower pole anatomical variables especially lower Infundibulo-pelvic angle and preferably first line treatment in patient with a lower pole stone has L-IPA >80 degrees and lower infundibular diameter of >5mm.